The efficacy of an allosteric modulator of the alpha 7 nicotinic acetylcholine receptor in a murine model of stroke - Hernandez, Katherine; Jones, Nathan; Ortega, Sterling B. (Frontiers in Neuroscience, 2025)
IntroductionIschemic strokes contribute significantly to cardiovascular-related deaths in the U.S., with current interventions limited to thrombolytic agents. However, these agents present challenges such as a limited therapeutic window, incomplete reperfusion rates, risk of transformation, reperfusion-induced inflammation, and a lack of promoting neuroprotection. We investigated an additional strategy in which prior studies indicated a neuroprotective role. Using a murine transient middle cerebral artery occlusion (tMCAO) model, we sought to evaluate the neurotherapeutic efficacy of a positive allosteric modulator of the alpha7 nicotinic acetylcholine receptor (α7-nAChR), PNU-120596 (PNU), specifically examining whether PNU would modulate stroke-induced neurological dysfunction and neuropathology, with modulation of neuroinflammation as a possible mechanism.MethodsYoung male C57BL/6J mice received a subcutaneous injection of 20mg/kg of vehicle (DMSO) or PNU-120596 immediately after reperfusion, and infarct area and Bederson score were analyzed 24 hours post-stroke. In the 72-hour post-stroke study, the animals were injected with 20mg/kg of PNU or vehicle subcutaneously immediately after reperfusion, followed by two additional doses of 10mg/kg of PNU or vehicle at 24 and 48 hours post-tMCAO. Seventy-two hours later, behavior function and infarct area were assessed.ResultsIn contrast to previous rat studies that demonstrated improvements in clinical outcomes, a single administration of PNU following stroke induction led to a reduction in acute neuropathology but did not produce a significant improvement in motor outcomes. Prolonged treatment showed no significant changes in acute neuropathology or sensorimotor function. Additionally, an assessment of neuroinflammation revealed no changes in CD4 T-cell cellularity or phenotype.DiscussionThese findings, alongside prior studies, suggest that the therapeutic efficacy of PNU may be contingent upon the timing of administration, dosage, and pharmacokinetics.